Ceramic sonotrodes for light alloy melt treatment - Puga, Hélder (2021)
Alloy melt treatment by ultrasonic vibration is a physical processing technique that has been gathering the support of the scientific community. The use of metallic sonotrodes for this purpose has been proven very efficient; however, it promotes melt inclusion by sonotrode erosion. Such an issue is being addressed by the use of ceramic sonotrodes in low-amplitude resonance. Given that these novel sonotrodes generally have complex shapes and low displacements, this study shows an innovative approach for their characterization. Based on scanning laser Doppler vibrometry, the signal processing Python-based script was used to map the overall resonant behavior of a tubular SiAlON sonotrode, and this route is able to characterize the complex shapes in low-amplitude and high-frequency radial resonance in resonant ceramic sonotrodes. Velocity time-domain profiles are shown to be dependent on the position, and even though the radial natural frequencies of ceramic sonotrodes have low amplitudes, they are proposed as an efficient tool for melt treatment. While characterizing the radial natural mode in ceramic sonotrodes, this study proves that their low-amplitude Lamb waves are responsible for the refinement of a-grains and secondary phases in light alloys.